Analysis of Pile Foundation Bearing Capacity based on SPT Data on the Pillar of the T. Nyak Makam Canal Bridge, Santan, Banda Aceh - Yuslinda, Yuslinda; Rani, Cut Meutia (Jurnal Teknik Sipil, 2025)
The T. Nyak Makam Canal Bridge in Santan, Banda Aceh, serves as a vital transportation link, spanning 135 meters in length and 24,6 meters in width. This study presents a comprehensive analysis of the pile foundation bearing capacity, utilizing Standard Penetration Test (SPT) data to evaluate the middle pillar"™s structural performance. The analysis adheres to established engineering standards, including SNI 03-1726-2002, SII 0136-80, SNI 03-6747-2002, and PPPJJR (1987). The bearing capacity was assessed using multiple methodologies: Meyerhof"™s method (169.99 tons), Briaud et al."™s method (280,52 tons), and the material strength method (349,561 tons), yielding an average bearing capacity of 266,69 tons. Given the total structural load of 36.778 tons, the foundation required 228 piles to ensure optimal load distribution and stability. Pile group settlement analysis via the Meyerhof method indicated a displacement of 0,1328 m, while stability assessments resulted in Î£Vi = 37.169,145 tons, Î£Hi = 4.191,265 tons, and Î£Mi = 838,669 t.m. The foundation consists of reinforced concrete piles with a diameter of 0,5 meters and a length of 26 meters, strategically arranged in 38 columns and 6 rows to maximize structural integrity. The findings confirm that the pile foundation exhibits high stability and meets all safety requirements, ensuring its suitability for long-term bridge performance.